An outbreak of dengue fever in children in the National Capital District of Papua New Guinea in 2016. (2nd July 2020) - Pulsan, Francis; Sobi, Kone; Anga, Gwenda; Vince, John; Duke, Trevor
ABSTRACT: Background: The first documented outbreak of dengue which included cases with haemorrhage occurred in Papua New Guinea in 2016. Aim: To document the presentation and outcome of children with dengue in Port Moresby. Methods: This prospective cross-sectional descriptive study was conducted in Port Moresby General Hospital during a 6-month period from 6 January to 6 July 2016. Altogether, 165 children aged 1–14 years who met the WHO criteria for probable dengue were assessed and treated. Clinical features, presence of warning signs and signs of severe dengue, date of onset, management and outcome were recorded. Blood specimens were collected for serological testing and full blood count. Results: The median age was 6 years (interquartile range 3–8). Eighty-eight (53%) children had no warning signs and were managed as outpatients. Of the 165 patients, 42 (25%) had abdominal pain, 28 (17%) had bleeding and 3 (2%) had clinical evidence of fluid accumulation. The median (IQR) lowest platelet count in those tested was 34 × 10 9 /L (22–54). Two children were transfused with packed red blood cells and one received a platelet transfusion. No child developed dengue shock and none died. Non-structural protein 1 (NS1) and dengue IgM were positive in 122/144 (85%) and 36/111 (32%) of blood samples, respectively. 150/151 blood samples tested for dengue were positive on one or more tests. Conclusion: There is the potential for future outbreaks of increased severity in Papua New Guinea. Surveillance, mosquito reduction initiatives and health education programmes are needed to reduce the impact of future outbreaks.